AI-Based Technique to Enhance Transient Response and Resiliency of Power Electronic Dominated Grids via Grid-Following Inverters - Hosseinzadehtaher, Mohsen; Zare, Alireza; Khan, Ahmad; Umar, Muhammad F.; D'silva, Silvanus; Shadmand, Mohammad B. (IEEE transactions on industrial electronics (1982), 2024)
This article presents a frequency restoration method to enhance power electronic dominated grid (PEDG) resiliency and transient response via redefining grid following inverters (GFLIs) role at the grid-edge. An artificial intelligence-based power reference correction (AI-PRC) module is developed for GFLIs to autonomously adjust their power setpoints during transient disturbances. A detailed analytical validation is provided that shows control rules in PEDG intrinsically follow the underlying dynamic of the swing-based machines to extend its stability boundary. Considering this fact, comprehensive transient and steady state-based mathematical models are used for constructing the learning database of the proposed AI-PRC. The proposed training approach can deal with grid's characteristics alterations and uncertainties. Thus, this approach incorporates PEDG's effective variables that shapes its dynamic response during transient disturbances. Subsequently, a neural network is trained by Bayesian regularization algorithm to realize the proposed AI-PRC scheme for frequency support via GFLIs. Several simulation and experimental case studies results validate the functionality of the proposed AI-PRC toward enhancing the PEDG's transient response and resiliency via GFLIs. The provided case studies demonstrate significant improvement in frequency restoration in response to transient disturbances.